2008
DOI: 10.1021/ja803299h
|View full text |Cite
|
Sign up to set email alerts
|

Acid Promoted Cinnamyl Ion Mobility within Peptide Derived Macrocycles

Abstract: We are developing methods that restrict the conformational mobility of peptides and related heteropolymers while simultaneously altering their properties. Our experiments occur as processes wherein a conserved, lipophilic reagent is activated in stages to form composite products with unprotected polyamides in parallel. For each starting oligomer, the goal is to create not one, but rather a collection of products. The intent is for those materials to retain molecular recognition elements of the biopolymer, yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 15 publications
(14 reference statements)
0
23
0
Order By: Relevance
“…1B) is reminiscent of a lignan monomer. It is a simplified, achiral form of a structure we described previously (51). The intent was to study large ring-forming reactions involving palladium π-allyl intermediates generated from the cinnamyl carbonate in this molecule.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B) is reminiscent of a lignan monomer. It is a simplified, achiral form of a structure we described previously (51). The intent was to study large ring-forming reactions involving palladium π-allyl intermediates generated from the cinnamyl carbonate in this molecule.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that decomposition of a cinnamyl carbonate within the template could capture pendant tyrosine residues to form cyclic ethers (51,54). This result followed from catalysis pioneered by Tsuji and Trost.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It also opens the possibility for multi-step sequences wherein the template modifies the oligomer more substantially and in increments. 18 …”
mentioning
confidence: 99%
“…Two uses of n-butyl lithium were noted, one in a very recent (2008) publication. 7,8 No uses of the much more air-reactive t-butyl lithium were found. It would be enlightening to know just how much experience the Harran research program has in working with extremely pyrophoric chemicals.…”
mentioning
confidence: 99%